2018
DOI: 10.4184/asj.2018.12.2.349
|View full text |Cite
|
Sign up to set email alerts
|

Does Vertical Ground Reaction Force of the Hip, Knee, and Ankle Joints Change in Patients with Adolescent Idiopathic Scoliosis after Spinal Fusion?

Abstract: Study DesignComparative cross-sectional study.PurposeWe measured the vertical ground reaction force (vGRF) of the hip, knee, and ankle joints during normal gait in normal patients, adolescent idiopathic scoliosis (AIS) patients with a Cobb angle <40° and in AIS patients with spinal fusion. We aimed to investigate whether vGRF in the aforementioned joints is altered in these three groups of patients.Overview of LiteraturevGRF of the lower limb joints may be altered in these groups of patients. Although it is kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Furthermore, malalignment of the bones and joints of the lower limbs and the spine of dancers with scoliosis and GJH might distort the direction of forces passing across the joints, and place them at higher risk to suffer PFP [54][55][56]. Any lower limb or spinal deformities may change the normal biomechanics and alter the forces to the knee [57], and that in turn may increase the risk for knee conditions [54,58,59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, malalignment of the bones and joints of the lower limbs and the spine of dancers with scoliosis and GJH might distort the direction of forces passing across the joints, and place them at higher risk to suffer PFP [54][55][56]. Any lower limb or spinal deformities may change the normal biomechanics and alter the forces to the knee [57], and that in turn may increase the risk for knee conditions [54,58,59].…”
Section: Discussionmentioning
confidence: 99%
“…Dancers with both phenomena had significantly reduced strength ability in the muscles around the knee. Yusof [57] suggested that reduced knee muscle strength in scoliotic subjects may exaggerate the interference of the biomechanics of the knee, as well as restrict the normal movement of the spinal segments and the loads across the knee joints, with increased risk for PFP. Yet, no previous study measured knee strength in scoliotic young dancers.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that the AIS group demonstrated balance deficits and increased fall risks compared to control subjects [5][6][7]. However, the vertical GRF is directly accompanied with gait asymmetry to mediolateral (M/L) and anteroposterior (A/P) planes when considering Cobb angle changes [8,9]. Several studies reported that AIS accompanies asymmetry between the left and right sides with a curved spine in the M/L plane and inertial asymmetry with uneven M/L distribution of the scoliotic changes [1,10].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies reported that the AIS group adjusted their Cobb angles, which are generally associated with greater asymmetry of GRF magnitudes in walking [9,13]. However, their studies did not carefully consider limb dominance or purposely excluded the frontal (M/L) plane of the GRF due to variations of the data in the AIS group [8,9,14]. Therefore, the results of these studies were limited since the convexities of the compensatory curves among the participants were varied and, more importantly, did not carefully consider homogeneous characteristics with the 3D GRF during gait.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of the ground reaction forces (GRFs) is used in a wide range of human movement studies, for instance, to investigate the internal forces in rehabilitation [1] or sports coaching [2,3], but importantly also to monitor the progression of musculoskeletal pathologies and neuromotor disorders [4,5]. When combined with spatiotemporal and kinematics parameters, GRFs allow the loading conditions acting on internal skeletal structures to be calculated [6], muscle activity to be assessed [7], and joint contact forces to be determined [8][9][10].…”
Section: Introductionmentioning
confidence: 99%